Association of psychotropic drug use with falls among older adults in Germany. Results of the German Health Interview and Examination Survey for Adults 2008-2011 (DEGS1). - Yong Du; Ingrid-Katharina Wolf; Hildtraud Knopf (PLoS ONE)
Purpose To investigate the association of psychotropic drug use with falls among older adults in Germany based on data from the National Health Interview and Examination Survey for Adults 2008-2011 (DEGS1). Methods DEGS1 collected data on drug use in the past 7 days and on falls occurred in the last 12 months. Study participants were older adults aged 65-79 years with complete data on drug use and falls (N = 1,833). Odds ratio (OR) and 95% confidence intervals (95% CI) were derived from logistic regression models adjusting for potential confounders including socio-demographic characteristics, health-related behaviors (alcohol drinking), body mass index and health conditions (frailty, vision impairment, disability, polypharmacy, blood pressure) as well as use of potential falls-risk-increasing drugs. SPSS complex sample methods were used for statistical analysis. Results Compared to people without falls, people with falls (n = 370) had a higher psychotropic drug use (33.1% vs. 20.7%, p < .001). After adjusting for potential confounders, use of psychotropic drugs overall was associated with a higher risk of falls (OR 1.64, 95% CI 1.14-2.37). This was particularly true for the use of synthetic psychotropic drugs (1.57, 1.08-2.28), antidepressants overall (2.88, 1.63-5.09) or synthetic antidepressants (2.66, 1.50-4.73), specifically, selective serotonin reuptake inhibitors (SSRIs) (6.22, 2.28-17.0). Similar results were found for recurrent falls. Conclusions Use of psychotropic drugs overall, especially synthetic antidepressants like SSRIs, is associated with higher risks of falls and recurrent falls among community dwelling older adults aged 65-79 years in Germany.